Rare earth doped Pt-based high-entropy intermetallic compound, preparation and application
By introducing rare earth metals into the hydroxide fuel cell catalyst, the electronic structure of Pt-based high-entropy intermetallic compounds is regulated, and the problems of high Pt usage and reduced performance in the catalyst are solved, and the catalyst activity and stability are significantly improved.
Patent Information
- Application Number
- CN202411777134.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The amount of Pt is used in the catalyst in the hydroxide fuel cell, which is expensive and difficult to obtain, and Pt desolates during the reaction, causing the problem of performance degradation.
By introducing rare earth metals, the electronic structure of Pt-based high-entropy intermetallic compounds is regulated, the activity and stability of the catalyst are improved, and the content of Pt is reduced.
The activity and stability of the catalyst were significantly improved, with mass activity reaching 2.0 A mg-1Pt. After 50,000 cycles of accelerated cyclic voltammetry test, its mass activity was reduced by only 8%, and it had ultra-high chemical stability.
Smart Images

Figure CN119601693A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a rare earth-doped Pt-based high-entropy intermetallic compound, and its preparation and application. Background Art
[0002] Hydrogen energy has attracted much attention due to its high energy density and the characteristics of only producing water after the reaction and not causing pollution to the environment. The use of hydrogen energy in actual production and life is of great significance to solving the current energy problem. Hydrogen-oxygen fuel cells are the key link in the application of hydrogen energy technology in actual production. The main reaction at the cathode of hydrogen-oxygen fuel cells is ORR (oxygen reduction reaction). Pt has a high reaction activity in ORR, but due to its high price and small amount in nature, it is not widely used in practice. Reducing the platinum (Pt) content while maintaining or even improving the activity and stability of the catalyst is an important challenge in the field of hydrogen-oxygen fuel cells. Alloying is an effective method to reduce the total amount of platinum required by combining platinum with other metal elements, and in some cases it can also improve the performance of the catalyst. Therefore, how to reduce the Pt content in the catalyst and improve the activity and stability of the catalyst in real life is an urgent problem to be solved in hydrogen-oxygen fuel cells. Summary of the invention
[0003] In view of the problem that the amount of Pt required for the catalyst used in hydrogen-oxygen fuel cells is large, the price is high and it is not easy to obtain, the present invention provides a rare earth-doped Pt-based high-entropy metal compound, preparation and application. The introduction of rare earth metals regulates the electronic structure of traditional Pt-based high-entropy metal compounds to a certain extent, and then regulates the adsorption energy of active sites to reaction intermediates during the reaction process, so that the activity and stability of the catalyst are greatly improved.
[0004] The mass activity of the rare earth-doped Pt-based high entropy intermetallic compound prepared by the present invention reaches 2.0 A mg -1 Pt , which is superior to traditional Pt-based high-entropy intermetallic compounds. It also has ultra-high stability. After 50,000 cycles of accelerated cyclic voltammetry testing, its mass activity only decreased by 8%.
[0005] One of the technical solutions of the present invention is to provide a method for preparing a rare earth-doped Pt-based high entropy intermetallic compound, comprising the following steps: (1) 200 mg of a carbon carrier containing a rare earth metal is ultrasonically dispersed in ultrapure water to obtain a suspension.
[0006] (2) A soluble platinum salt, a soluble nickel salt, a soluble cobalt salt, a soluble iron salt, and a soluble copper salt in a molar ratio of 4:1:1:1:1 are added to the suspension, wherein the mass of the soluble platinum salt is 40 mg.
[0007] (3) After stirring the mixed suspension for 12 h, the solvent was removed by rotary evaporation to obtain a black solid.
[0008] (4) Calcine the obtained black solid.
[0009] (5) The calcined black solid is etched to obtain a rare earth-doped Pt-based high entropy intermetallic compound, wherein the mass fraction of Pt is 20.1-21.14%.
[0010] Furthermore, the carbon carrier containing rare earth metals in step (1) is obtained by calcining a rare earth metal organic framework, which specifically comprises the following steps: 1) Dissolve trimesic acid (BTC) in a mixed solution of water and N,N-dimethylformamide (DMF) to obtain solution A.
[0011] 2) Dissolve the rare earth salt in a mixed solution of water and DMF to obtain solution B.
[0012] 3) Pour solution A into solution B, stir at 90 °C for 3 h and collect the precipitate.
[0013] 4) The obtained precipitate was calcined at 900 °C for 1 h under an argon atmosphere to obtain a carbon support containing rare earth metals.
[0014] Furthermore, the rare earth salt is one of scandium nitrate hydrate, yttrium nitrate hexahydrate, lanthanum chloride heptahydrate, anhydrous cerium chloride, praseodymium nitrate hexahydrate, neodymium nitrate hexahydrate, samarium chloride hexahydrate, europium nitrate hexahydrate, gadolinium chloride hexahydrate, terbium nitrate hexahydrate, dysprosium chloride hexahydrate, holmium nitrate pentahydrate, erbium nitrate hexahydrate, thulium chloride hexahydrate, ytterbium nitrate pentahydrate, and lutetium nitrate hydrate.
[0015] Furthermore, in step (2), the soluble platinum salt is chloroplatinic acid hexahydrate, the soluble nickel salt is nickel chloride hexahydrate, the soluble cobalt salt is cobalt chloride hexahydrate, the soluble iron salt is ferrous chloride tetrahydrate, and the soluble copper salt is cupric chloride dihydrate.
[0016] Furthermore, the calcination conditions in step (4) are to use a tubular furnace in an atmosphere of hydrogen:argon volume ratio of 5:95, raise the temperature to 900°C at a heating rate of 10°C / min, maintain for 2 h, and then cool to 700°C at a cooling rate of 10°C / min, and maintain for 6 h.
[0017] Furthermore, the etching condition in step (5) is etching in a 0.1 M perchloric acid aqueous solution for 12 h.
[0018] The second technical solution of the present invention is to provide a rare earth-doped Pt-based high entropy intermetallic compound prepared by the above preparation method.
[0019] Due to the unique oxygen-affinity of rare earth metals, the introduction of rare earth metals will regulate the adsorption strength of the catalyst to oxygen species to a certain extent, thereby improving the catalytic activity and stability of Pt, and can to a certain extent solve the "high platinum" problem and the problem of performance degradation caused by Pt desolvation during the reaction.
[0020] At the same time, the present invention introduces rare earth elements in the form of metal organic frameworks, realizes atomic-level dispersion of rare earth metals on carbon substrates, and can achieve strong coupling between rare earth and Pt-based nanoparticles. When rare earth metal atoms or small clusters are combined with Pt nanoparticles, strong electronic interactions can be formed between them. This interaction helps to adjust the electronic structure of Pt nanoparticles and further improve their catalytic performance.
[0021] The third technical solution of the present invention is to provide an application of the above-mentioned rare earth-doped Pt-based high entropy metal compound in acidic oxygen reduction (ORR) and hydrogen fuel cell cathode materials.
[0022] Beneficial effects of the present invention: (1) The Pt content in the platinum-based catalyst was effectively reduced, which to some extent solved the problem of "high platinum" and the problem of performance degradation caused by Pt desolvation during the reaction, and significantly improved the catalytic activity and stability. After 50,000 cycles of accelerated cyclic voltammetry testing, its mass activity was only reduced by 8%, showing ultra-high chemical stability.
[0023] (2) The prepared rare earth-doped Pt-based high entropy intermetallic compounds have excellent mass activity, and the mass activity of Gd-Pt4FeCoNiCu reaches 2.0 A mg -1 The mass activity of Pt, Nd-Pt4FeCoNiCu reached 1.8 A mg -1 Pt, are superior to the traditional Pt-based high entropy intermetallic compound Pt4FeCoNiCu / C. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is the X-ray diffraction spectrum of Examples 1-16 and Comparative Example 1.
[0025] Figure 2 These are the electrochemical polarization curves of Example 1, Example 2, Example 3, Example 5, Example 6, Example 7, Example 10, Example 11, Example 13, Example 14, Example 16 and Comparative Example 1 as ORR catalysts.
[0026] Figure 3 This is a scanning transmission electron microscope (STEM) image of Example 1.
[0027] Figure 4This is the energy dispersive X-ray spectrum of Example 1.
[0028] Figure 5 This is a high-resolution transmission electron microscopy image (HRTEM) of Example 1.
[0029] Figure 6 This is a stability test performed on Example 1.
[0030] Figure 7 The activity performance of Example 1 in a membrane electrode device. DETAILED DESCRIPTION
[0031] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.
[0032] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.
[0033] The embodiments of the present invention are further described below with reference to a plurality of embodiments.
[0034] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0035] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0036] Example 1 (1) Gd-Pt4FeCoNiCu was prepared by the following method: 437.7 mg of BTC was weighed and dissolved in 100 mL of a mixed solution of water and DMF to obtain solution A; 588.7 mg (GdCl3·6H2O) was weighed and dissolved in 100 mL of a mixed solution of water and DMF with a volume ratio of 1:1 to obtain solution B; A was poured into B, stirred at 90 °C for 3 h, and the precipitate was collected. The obtained precipitate was calcined at 900 °C for 1 h under an argon atmosphere to obtain a Gd-loaded carbon support;
[0037] (2) Dissolve 200 mg of the carrier in water and treat with ultrasound for 30 min to obtain a suspension. Then, add H2PtCl6·6H2O, NiCl2·6H2O, CoCl2·6H2O, FeCl2·4H2O, and CuCl2·2H2O in the suspension in a molar ratio of 4:1:1:1:1. The mass of H2PtCl6·6H2O is 40 mg. After stirring for 12 h, the solvent is removed by rotary evaporation to obtain a black solid. The obtained black solid was heated to 900 °C at a heating rate of 10 °C / min in an atmosphere of hydrogen and argon (hydrogen:argon = 5:95), maintained for 2 h, then cooled to 700 °C at a cooling rate of 10 °C / min, maintained for 6 h. After natural cooling, it was etched in a 0.1 M perchloric acid solution for 12 h to obtain the final product Gd-Pt4FeCoNiCu catalyst, in which the mass fraction of Pt was 20.1%.
[0038] Figure 3 This is a scanning transmission electron microscope (STEM) picture of this embodiment. Through the STEM picture, it can be seen that the intermetallic compound particles are densely distributed on the carrier, and the distribution is also very uniform. By calculating the average particle size of the area, the average particle size is about 3.7 nm. The smaller the particle size, the greater the utilization rate of Pt is improved.
[0039] Figure 4 From the energy dispersive X-ray spectrum (EDX) of this embodiment, it can be seen that Gd, Pt, Fe, Co, Ni, and Cu are distributed in individual intermetallic compound particles, proving that Gd has been successfully introduced into the high entropy system.
[0040] Figure 5 This is a high-resolution transmission electron microscopy image (HRTEM) of this example, which further proves the high crystallinity of Gd-Pt4FeCoNiCu. Since the image brightness is related to the atomic number, the brighter atomic layer can be confirmed to be Pt from the alternating layers of darker and brighter atoms. The outer layer is covered by a Pt layer, proving that a Pt-based high-entropy intermetallic compound with a core-shell structure has been successfully synthesized. Through the HRTEM image, the (001) crystal plane of Pt can be clearly observed, and the lattice spacing is 3.590 Å.
[0041] Figure 6 Stability test performed for this example. The Gd-Pt4FeCoNiCu catalyst was subjected to accelerated degradation in an O2-saturated 0.1 M HClO4 solution at a scan rate of 200 mV / s over the range of 0.6 V to 0.95 V. After 50,000 CV scans, its mass activity decreased by only 8% (a) and there was almost no attenuation in the half-wave potential (b).
[0042] Figure 7 This is the hydrogen-oxygen (air) fuel cell test for this example. At 80 °C, 1 bar pressure, cathode loading 0.1 mg Pt cm -2 Under the test conditions of H2 / O2 flow rate of 500 / 1000 sccm, the maximum power density of the hydrogen-oxygen membrane electrode assembled with Gd-Pt4FeCoNiCu catalyst reached 2.2 W cm -2 (a) above. Under air conditions, the maximum power reached 1.2 W cm -2 (b).
[0043] Embodiment 2: Same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of yttrium nitrate hexahydrate (Y(NO3)3·6H2O), and the product obtained is a carbon support loaded with yttrium; (2) 200 mg of yttrium-loaded carbon support was dissolved in water and ultrasonically treated for 30 min to obtain a suspension. Then, H2PtCl6·6H2O, NiCl2·6H2O, CoCl2·6H2O, FeCl2·4H2O, and CuCl2·2H2O were added to the suspension in a molar ratio of 4:1:1:1:1. The mass of H2PtCl6·6H2O was 40 mg. After stirring for 12 h, the solvent was removed by rotary evaporation to obtain a black solid. The obtained black solid was heated to 900 °C at a heating rate of 10 °C / min in an atmosphere of hydrogen and argon (hydrogen:argon = 5:95), maintained for 2 h, then cooled to 700 °C at a cooling rate of 10 °C / min, maintained for 6 h. After natural cooling, it was etched in a 0.1 M perchloric acid solution for 12 h to obtain the final product Y-Pt4FeCoNiCu catalyst with a Pt mass fraction of 21.14%.
[0044] Embodiment 3: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of lanthanum chloride heptahydrate (LaCl3·7H2O), and the final product La-Pt4FeCoNiCu is obtained.
[0045] Embodiment 4: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of anhydrous cerium chloride (CeCl3), and the final product Ce-Pt4FeCoNiCu is obtained.
[0046] Embodiment 5: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of praseodymium nitrate hexahydrate (Pr(NO3)3·6H2O), and the final product Pr-Pt4FeCoNiCu is obtained.
[0047] Embodiment 6: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of neodymium nitrate hexahydrate (Nd(NO3)3·6H2O), and the final product Nd-Pt4FeCoNiCu is obtained.
[0048] Embodiment 7: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of samarium chloride hexahydrate (SmCl3·6H2O), and the final product Sm-Pt4FeCoNiCu is obtained.
[0049] Embodiment 8: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of europium nitrate hexahydrate (Eu(NO3)3·6H2O), and the final product Eu-Pt4FeCoNiCu is obtained.
[0050] Embodiment 9: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of scandium nitrate hydrate (Sc(NO3)3·xH2O), and the final product Sc-Pt4FeCoNiCu is obtained.
[0051] Embodiment 10: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of terbium nitrate hexahydrate (Tb(NO3)3·6H2O), and the final product Tb-Pt4FeCoNiCu is obtained.
[0052] Embodiment 11: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of dysprosium chloride hexahydrate (DyCl3·6H2O), and the final product Dy-Pt4FeCoNiCu is obtained.
[0053] Embodiment 12: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of holmium nitrate pentahydrate (Ho(NO3)3·5H2O), and the final product Ho-Pt4FeCoNiCu is obtained.
[0054] Embodiment 13: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of erbium nitrate hexahydrate (Er(NO3)3·6H2O), and the final product Er-Pt4FeCoNiCu is obtained.
[0055] Embodiment 14: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of thulium chloride hexahydrate (TmCl3·6H2O), and the final product Tm-Pt4FeCoNiCu is obtained.
[0056] Embodiment 15: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of ytterbium nitrate pentahydrate (Yb(NO3)3·5H2O), and the final product Yb-Pt4FeCoNiCu is obtained.
[0057] Embodiment 16: The same as Example 1, except that the rare earth salt added in step 1 is an equimolar amount of lutetium nitrate hydrate (Lu(NO3)3·xH2O), and the final product Lu-Pt4FeCoNiCu is obtained.
[0058] Comparative Example 1: Same as Example 1, except that a KJ-600 carbon substrate is used as a carrier, and the final product is Pt4FeCoNiCu / C.
[0059] according to Figure 1 X-ray diffraction spectra of Examples 1-16 and Comparative Example 1. It can be seen that most of the prepared rare earth series Pt-based high entropy intermetallic compounds show good matching with the standard card and have high crystallinity. In addition, after the introduction of rare earth elements, the lattice peak does not shift significantly relative to Pt4FeCoNiCu / C, indicating that the introduction of rare earth metals has not broken the overall lattice structure of traditional Pt-based intermetallic compounds.
[0060] Figure 2 The electrochemical polarization curves of Example 1, Example 2, Example 3, Example 5, Example 6, Example 7, Example 10, Example 11, Example 13, Example 14, Example 16 and Comparative Example 1 prepared by the present invention. The ORR performance of Example 1, Example 2, Example 3, Example 5, Example 6, Example 7, Example 10, Example 11, Example 13, Example 14, Example 16 and Comparative Example 1 was evaluated in an O2-saturated 0.1 M HClO4 solution using a rotating disk electrode method (RDE). Figure 2 The polarization curves of all catalysts recorded at a rotation speed of 1600 rpm and a scan rate of 10 mV / s are shown. It can be seen that the activity of rare earth metal-doped Pt-based high entropy metal compounds is greatly improved compared with traditional Pt-based high entropy metal compounds, especially the Pt-based rare earth high entropy metal compound catalysts represented by rare earth metal gadolinium (Gd) and rare earth metal neodymium (Nd), with mass activities reaching 2.0 A mg Pt -1 and 1.8 A mg Pt -1 .
[0061] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.
Claims
1. A method for preparing a rare earth-doped Pt-based high entropy intermetallic compound, characterized in that: The following steps are involved: (1) Ultrasonic dispersion of 200 mg of a rare earth-containing carbon carrier in ultrapure water to obtain a suspension; (2) adding a soluble platinum salt, a soluble nickel salt, a soluble cobalt salt, a soluble iron salt, and a soluble copper salt in a molar ratio of 4:1:1:1:1 into the suspension, wherein the mass of the soluble platinum salt is 40 mg; (3) After stirring the mixed suspension for 12 h, the solvent was removed by rotary evaporation to obtain a black solid; (4) calcining the obtained black solid; (5) The calcined black solid is etched to obtain a rare earth-doped Pt-based high entropy intermetallic compound, wherein the mass fraction of Pt is 20.1-21.14%.
2. The preparation method according to claim 1, characterized in that: The rare earth-containing carbon carrier in step (1) is obtained by the following steps: (1) Dissolve trimesic acid (BTC) in a mixed solution of water and N,N-dimethylformamide (DMF) to obtain solution A; (2) Dissolving the rare earth salt in a mixed solution of water and DMF to obtain solution B; (3) Pour solution A into solution B, stir at 90 °C for 3 h, and collect the precipitate; (4) The obtained precipitate was calcined at 900 °C for 1 h under an argon atmosphere to obtain a carbon support containing rare earth metals.
3. The preparation method according to claim 2, characterized in that: The rare earth salt is one of scandium nitrate hydrate, yttrium nitrate hexahydrate, lanthanum chloride heptahydrate, anhydrous cerium chloride, praseodymium nitrate hexahydrate, neodymium nitrate hexahydrate, samarium chloride hexahydrate, europium nitrate hexahydrate, gadolinium chloride hexahydrate, terbium nitrate hexahydrate, dysprosium chloride hexahydrate, holmium nitrate pentahydrate, erbium nitrate hexahydrate, thulium chloride hexahydrate, ytterbium nitrate pentahydrate, and lutetium nitrate hydrate.
4. The preparation method according to claim 1, characterized in that: The soluble platinum salt in step (2) is chloroplatinic acid hexahydrate, the soluble nickel salt is nickel chloride hexahydrate, the soluble cobalt salt is cobalt chloride hexahydrate, the soluble iron salt is ferrous chloride tetrahydrate, and the soluble copper salt is cupric chloride dihydrate.
5. The preparation method according to claim 1, characterized in that: The calcination conditions in step (4) are as follows: using a tubular furnace in an atmosphere of hydrogen:argon volume ratio of 5:95, heating to 900°C at a heating rate of 10°C / min, maintaining for 2 h, and then cooling to 700°C at a cooling rate of 10°C / min, maintaining for 6 h.
6. The preparation method according to claim 1, characterized in that: The etching conditions in step (5) are etching in a 0.1 M perchloric acid aqueous solution for 12 h.
7. A rare earth-doped Pt-based high entropy intermetallic compound prepared by the preparation method as claimed in claim 1.
8. Use of the rare earth doped Pt-based high entropy intermetallic compound as claimed in claim 7 in acidic oxygen reduction and hydrogen fuel cell cathode materials.
Citation Information
Patent Citations
Intermetallic compound composite material and preparation method thereof and application of intermetallic compound composite material and preparation method thereof
CN109706364A
Ultra-small multicomponent alloy composite material and preparation method and application thereof
CN110064423A
Rare earth gadolinium doped high-stability platinum-based catalyst as well as preparation method and application thereof
CN117766789A
Rare earth element doped carbon nitride loaded noble metal electrocatalyst as well as preparation method and application thereof
CN118825307A
Method for producing high entropy alloy, method of use of high entropy alloy, high entropy alloy catalyst, and high entropy alloy
JP2024036067A